Understanding the support experiences of families of children with autism and sensory processing difficulties: A qualitative study - Sarah Milosevic; Lucy Brookes‐Howell; Elizabeth Randell; Rhys Williams‐Thomas; Sue Delport; Monica Busse; David Gillespie; Alka S. Ahuja; Anne Marie McKigney; Eleni Glarou; Rachel McNamara (Wiley, 2022)
Abstract Background Support, such as information, advice and therapies, can play a vital role in the lives of families of autistic children. However, little is known about the support experiences of UK parents and carers. Aim To explore experiences of and access to support for families of children with autism and sensory processing difficulties, from the perspective of parents and carers. Methods Semi‐structured, timeline‐assisted interviews were conducted with parents/carers of 30 children aged 5-11, exploring experiences of support. Framework analysis was used to identify themes in the interview data. Results Support varied widely and was not accessed equitably. Specialist autism support, together with support from other parents and voluntary organizations, was perceived as more useful than statutory and nonspecialist provision. Unmet support needs included an ongoing point of contact for information and advice for parents, and access to direct therapy and specialist mental health provision for children. Conclusions Findings emphasize the need for a clear pathway of support following autism diagnosis, autism‐specific training for professional service providers and specialist provision tailored to the needs of autistic children. Patient or Public Contribution An advisory group of four parents of children with autism provided feedback on study procedures and materials, including participant information sheets and timeline completion instructions.